What do psychodynamic therapists make of their reveries in the therapeutic encounter? A constructivist grounded theory study - Stokes, FM; Ross, A (Routledge, 2019)
The therapist’s mind can wander to daydreams, fantasies and preoccupations: mental events termed “reveries” in this study. As therapists attend to the current of their thought in the therapeutic encounter, the question of how to approach their reveries can arise. This qualitative study used semi-structured interviews with nine qualified psychodynamic therapists to investigate therapists’ attitudes to reveries. The research design and analysis followed the principles of Charmaz’s [Charmaz, K. (2006). Constructing grounded theory: A practical guide through qualitative analysis. London: Sage; Charmaz, K. (2014). Constructing grounded theory (2nd ed.). London: Sage] constructivist grounded theory. Results showed that therapists experienced diverse reveries sometimes felt to yield deeper clinical understanding. Reveries were also seen to have a “freeing-up” function for the therapist and patient, and to require mental freedom to operate. Implications for theoretical understanding and recommendations for clinical technique are discussed.